Highly Luminous Ba2SiO4-δN2/3δ:Eu2+ Phosphor for NUV-LEDs: Origin of PL-Enhancement by N3--Substitution - Kim, Donghyeon; Kim, Tae Hun; Hong, Tae Eun; Bae, Jong Seong; Kim, Chang Hae; Kim, Jaegyeom; Kim, Seung Joo; Jeon, Ki Wan; Park, Jung Chul (Materials, 2020)
Ba2SiO4-δN2/3δ:Eu2+ (BSON:Eu2+) materials with different N3- contents were successfully prepared and characterized. Rietveld refinements showed that N3 ions were partially substituted for the O2- ions in the SiO4-tetrahedra because the bond lengths of Si-(O, N) (average value = 1.689 A) were slightly elongated compared with those of Si-O (average value = 1.659 A), which resulted in the minute compression of the Ba(2)-O bond lengths from 2.832 to 2.810 A. The average N3 contents of BSON:Eu2++ phosphors were determined from 100 nm to 2000 nm depth of grain using a secondary ion mass spectrometry (SIMS): 0.064 (synthesized using 100% α-Si3N4), 0.035 (using 50% α-Si3N4 and 50% SiO2), and 0.000 (using 100% SiO2). Infrared (IR) and X-ray photoelectron spectroscopy (XPS) measurements corroborated the Rietveld refinements: the new IR mode at 850 cm-1 (Si-N stretching vibration) and the binding energy at 98.6 eV (Si-2p) due to the N3-substitution. Furthermore, in UV-region, the absorbance ofN3--substituted BSON:Eu2++ (synthesized using 100% α-Si3N4) phosphor was about two times higher than that of BSO:Eu2++ (using 100% SiO2). Owing to the N3- substitution, surprisingly, the photoluminescence (PL) and LED-PL intensity of BSON:Eu2++ (synthesized using 100% α-Si3N4) was about 5.0 times as high as that of BSO:Eu2++ (using 100% SiO2). The compressive strain estimated by the WilliamsonHall (W-H) method, was slightly increased with the higher N3- content in the host-lattice of Ba2SiO4, which warranted that the N3- ion plays an important role in the highly enhanced PL intensity of BSON:Eu2++ phosphor. These phosphor materials could be a bridgehead for developing new phosphors and application in white NUV-LEDs field.
Keywords: Average values; Compressive strain; Host lattice; Phosphor materials; PL intensity; SiO4 tetrahedra; Stretching vibrations; Williamson-Hall; Ba2SiO4:Eu2++; IR; N3- substitution; PL; SIMS; XPS